Pengaruh Program Dakwah Peduli Umat Pada Youtube Lk Channel Terhadap Pemahaman Pesan Agama Subscriber Lk Channel - ayu, Ayu Ulandari (Journal of Media and Communication Studies, 2024)
This study aims to find how much influence the Dakwah Peduli Umat program of Lk Channel youtube has on understanding the religious massage of Lk Channel subscribers. In this study using quantitative research methods with type of Ex-post Facto, this research was conducted by relying on an instrument in form of a closed quetionnaire so that the result were in the form of numbers such as percentages. The result of the research that we obtained from the variabel X (knowladge about Dakwah Peduli Umat Program) it is known that total obtained from Lk Channel subscriber questionnaire was obtained as many 578 respondents, wich meants it is medium category (416,6 – 583,3). The result of the research that we obtained from the variabel X (knowladge about Understanding the Religious Massage) it is known that total obtained from Lk Channel subscriber questionnaire was obtained as many 554 respondents, wich meants it is medium category (416,6 – 583,3). Based on this, it can be said that influence the Dakwah Peduli Umat program of Lk Channel youtube has on understanding the religious massage of Lk Channel subscribers is in the medium category and can be said to be effective. This means that according to Lk Channel Subscriber in dakwah peduli umat program, that there is an influence they get of dakwah peduli umat program caring for the people to understand the religious massage of Lk Channel youtube. However, respondents are still at stage of only knowing dan understanding, also not yet a high category related to understanding and knowladge and is still in medium category. Based on experience in carrying out research, in this section, the researcher wants to provide suggestions, we hope that it can be useful for further research.